2021
DOI: 10.3847/1538-4357/abe30d
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Warm Carbon-chain Chemistry and Interstellar Irradiation of Star-forming Cores

Abstract: Some observations of warm carbon-chain chemistry (WCCC) cores indicate that they are often located near the edges of molecular clouds. This finding may suggest that WCCC is promoted in star-forming cores exposed to radiation from the interstellar medium. We aim to investigate the chemistry of carbon chains in such a core. A chemical simulation of a gas parcel in a low-mass star-forming core with a full level of irradiation by interstellar photons and cosmic rays was compared to a simulation of a core receiving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 103 publications
2
20
0
Order By: Relevance
“…If this trend is genuine, following the interpretation of the ratio of carbon chain to methanol by Lattanzi et al (2020), 1390 would be the most highly irradiated of our three targets. This is in line with the fact that it lies at the border of the λ Ori HII region, but contradicts the conclusion derived from the comparison of c-C 3 H 2 and C 4 H abundances in the model by Kalvāns (2021) and in our data. This discrepancy may be a sign of the model limitations in the prestellar phase.…”
Section: Carbon Chainssupporting
confidence: 67%
See 4 more Smart Citations
“…If this trend is genuine, following the interpretation of the ratio of carbon chain to methanol by Lattanzi et al (2020), 1390 would be the most highly irradiated of our three targets. This is in line with the fact that it lies at the border of the λ Ori HII region, but contradicts the conclusion derived from the comparison of c-C 3 H 2 and C 4 H abundances in the model by Kalvāns (2021) and in our data. This discrepancy may be a sign of the model limitations in the prestellar phase.…”
Section: Carbon Chainssupporting
confidence: 67%
“…Although the interest in carbon chains has somewhat shifted to protostellar objects following the discovery of warm carbon-chain chemistry (WCCC) in the envelope of a young stellar object (Sakai et al 2007), the understanding of carbon-chain chemistry in starless and prestellar cores remains of high interest for several reasons. The presence of carbon chains near protostars may partly originate in the prestellar chemistry (Aikawa et al 2020;Kalvāns 2021), but more importantly for our study, the current understanding is that the chemical differentiation observed from the comparison of carbon chains and oxygen-rich species such as methanol is caused by different physical (e.g. gas temperature) and environmental conditions.…”
Section: Carbon Chainsmentioning
confidence: 83%
See 3 more Smart Citations